Tantangan Pemimpin Perempuan pada Rehabilitas Narkoba Trisna Health Voluntary Center Tulungagung - Harlis Setiyowati; Muhammad Alfathan Harriz; Indah Sulistyoningsih; Nurhaliza Vania Akbariani (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2022)
The success of a female leader will depend on her self-confidence in her abilities and abilities. Women leaders who are business owners often have a strong drive to be able to realize their potential and contribute to society. The Trisna Health Voluntary Center (HVC) Drug Victims Rehabilitation Foundation is run by Mrs. Triswati Sasmito. The HVC Foundation offers social rehabilitation as well as assistance or recovery to substance misuse victims. 1) How to engage and participate in challenges as a female leader is the primary focus of this study. 2) Women leaders' management and implementation of drug rehabilitation initiatives experience. 3) Observe the difficulties faced by female executives in other industries. The conclusions include: 1) How to connect and participate in challenges as a female leader, specifically with a deep touch such that it has a favorable impact on the anticipated results, including speedier recovery and regaining health and even being able to join with family and the local community. 2) The expertise of female company owners in the field of drug rehabilitation, namely in the administration and execution of therapeutic activities utilizing Therapeutic Communities and running Drug Prevention Education (DPE) programs 3) Women leaders in different industries have encountered a variety of difficulties, depending on their respective fields and nations, but they have managed to persevere and keep up their good work. Women still don't participate enough in politics. To donate their own quotas for national growth, it is advised that more women participate.